Cardiac Pacing in Sub-Saharan Africa JACC International - (:unkn) unknown (My University, 2019)
Many parts of the developing world, especially Sub-Saharan Africa, completely lack access to cardiac pacing. The authors initiated a multinational program to implement cardiac pacing in 14 countries in Sub-Saharan Africa (1996 to 2018), aiming to eventually build self-sustainable capacity in each country. This was based on an "on-site training" approach of performing procedures locally and educating local health care teams to work within resource-limited settings, with prospective evaluation of the program. In 64 missions, a total of 542 permanent pacemakers were implanted. In 11 of these countries, the first pacemaker implant in the country was through the mission. More than one-half of those initially listed as suitable died before the mission(s) arrived. The proportion of implantations that were completely handled by local teams increased from 3% in 1996 to 98% in 2018. These findings demonstrate the feasibility and effectiveness of a proctorship-based approach to the development of local cardiac pacing capabilities in Sub-Saharan African nations.
Keywords: African Research